STRATEGI PENDEKATAN PSIKOLOGI DALAM MEMBANTU SISWA MENGATASI TANTANGAN BELAJAR - T. Hasballah; Loeziana Uce (Adisam Publisher, 2024)
This research explores the application of psychological strategies to help students overcome learning challenges. The research focuses on five main strategies: individual counselling, motivation development, stress management, limited resources, and their integration in the school context. The research highlights that individual counselling provides emotional support, enabling students to address personal issues that aflect their learning. Motivation development, by enhancing intrinsic motivation, promotes greater engagement and perseverance in learning. Stress management techniques, including mindfulness and relaxation strategies, proved eflective in reducing anxiety and improving student focus. However, resource limitations often hinder the eflective implementation of these strategies. The findings of this study suggest that a holistic approach that integrates these psychological interventions into the school environment is essential to support students' academic and emotional development. This research contributes to the field of educational psychology by emphasising the importance of psychological support systems in improving student performance and well-being. Based on the results, recommendations are provided for further research and practical application in schools, highlighting the need for comprehensive training for educators and counsellors as well as the allocation of adequate resources to eflectively implement these strategies in educational settings.